Fistuloclysis: An Interprofessional Approach to Nourishing the Fistula Patient. Issue 5 (September 2015) - Willcutts, Kate; Mercer, David; Ziegler, Jane
Abstract : BACKGROUND: Enteric fistulas can be classified as enterocutaneous and/or enteroatmospheric. Both are devastating complications of bowel disease, abdominal surgery, and/or open abdomen. Enteric fistulas are associated with a mortality rate varying from 1% to 33%; the main cause of death is sepsis. Coordinated and skillful efforts of an interprofessional team are required in customizing successful treatment regimens appropriate to each patient's unique clinical scenario. CASE STUDY: A 65-year-old white woman experienced an enteroatmospheric fistula patient after ventral hernia repair. Care of this patient was based on the complementary relationship between professionals from 2 disciplines: the wound and ostomy continence nurse (WOC nurse) and the nutrition support registered dietitian/nutritionist. Working together, they developed a comprehensive wound, ostomy, and nutritional plan. Initially, the patient received parenteral nutrition exclusively. After the fistula tract was clearly defined, a feeding tube was placed into the distal limb of the fistula, and she received nourishment via a fistuloclysis (ie, enteral feedings administered via the fistula). A special wound management system was created to contain fistula output while allowing feeding through the distal limb of the fistula. CONCLUSION: Enterocutaneous and enteroatmospheric fistulas originating from the small bowel present a management challenge to the entire healthcare team. WOC nurses are often called upon to meet the challenge of maintaining skin health while promoting dignity and function. Nutrition support via registered dietitian/nutritionists play a critical role in managing the nutrition regimen for these patients. In this case, the use of fistuloclysis met the patient's nutritional needs while avoiding the risks associated with parenteral nutrition.